2014
DOI: 10.3855/jidc.4616
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus GII.4 antibodies in the Portuguese population

Abstract: Introduction: Norovirus GII.4 is the leading cause of outbreaks of acute and sporadic acute gastroenteritis worldwide. Information on the prevalence of norovirus in Portugal is scarce or null. Methodology: We used a GII.4 norovirus virus-like particle-based enzyme immune assay to measure the seropositivity rate of GII.4 norovirus. Results: A total of 342 (70%) out of 473 serum samples tested positive for anti-GII.4 norovirus IgG. No statistically significant differences were found between regions, sex and age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Antibodies to GII.4 NoV were detected in 70% of sera samples collected from Portuguese adults 54 whereas the seroprevalence of IgG against GI.4, GII.3, and GII.4 NoV genotypes was 84.1%, 76.3%, and 94.5%, respectively in a cohort of Koreans. 55 This study reported low levels of antibodies among <23-month age group.…”
Section: Viral Shedding Natural Infection With Nov and Seroprotectionmentioning
confidence: 99%
“…Antibodies to GII.4 NoV were detected in 70% of sera samples collected from Portuguese adults 54 whereas the seroprevalence of IgG against GI.4, GII.3, and GII.4 NoV genotypes was 84.1%, 76.3%, and 94.5%, respectively in a cohort of Koreans. 55 This study reported low levels of antibodies among <23-month age group.…”
Section: Viral Shedding Natural Infection With Nov and Seroprotectionmentioning
confidence: 99%
“…As an alternative approach to pathogen detection in stool samples, serology is commonly used to estimate the prevalence in a population. Serological studies representing different populations globally have identified a prevalence of antibodies to noroviruses ranging between 80% to 100% in adults (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Most serology studies used virus-like particles (VLPs) of GI.1, GII.3, and GII.4 (8,16,24,25), and only a few have investigated antibody responses to other norovirus genotypes (14,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Serological studies representing different populations globally have identified a prevalence of antibodies to noroviruses ranging between 80% to 100% in adults (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Most serology studies used virus-like particles (VLPs) of GI.1, GII.3, and GII.4 (8,16,24,25), and only a few have investigated antibody responses to other norovirus genotypes (14,26,27). These VLPs consist of 90 major capsid protein (VP1) dimers and are antigenically comparable to native virions (28).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 GI and GII are most commonly involved in human outbreaks, with genotype GII.4 responsible for about 60% of the overall disease burden. 8 Epidemiological data on human NoV in Portugal includes surveillance studies, [9][10][11] reports of outbreaks caused by contaminated food [12][13][14][15] and studies of recreational waters. 16 RVs are known as the major aetiological agent of paediatric AGE.…”
Section: Introductionmentioning
confidence: 99%